2018
DOI: 10.1111/jpy.12816
|View full text |Cite
|
Sign up to set email alerts
|

Light capture and pigment diversity in marine and freshwater cryptophytes

Abstract: Phenotypic traits associated with light capture and phylogenetic relationships were characterized in 34 strains of diversely pigmented marine and freshwater cryptophytes. Nuclear SSU and partial LSU rDNA sequence data from 33 of these strains plus an additional 66 strains produced a concatenated rooted maximum likelihood tree that classified the strains into 7 distinct clades. Molecular and phenotypic data together support: (i) the reclassification of Cryptomonas irregularis NIES 698 to the genus Rhodomonas, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 50 publications
4
52
0
Order By: Relevance
“…Thirty-two are named species, two are different strains of one species (Cryptomonas pyrenoidifera), eight are strains identified to a genus and two are unidentified strains; in total, these strains represent at least 12 genera (electronic supplementary material, table S1). Phenotypic characteristics (whole-cell absorption spectra, cell size measurements, pigment concentrations, phycobiliprotein absorption spectra and PUR values) for 33 of the strains in this study were previously reported in Cunningham et al [14]. Specific characteristics of those strains plus the nine additional strains that we measured are listed in the electronic supplementary material, table S1.…”
Section: (A) Data Collectionmentioning
confidence: 73%
See 4 more Smart Citations
“…Thirty-two are named species, two are different strains of one species (Cryptomonas pyrenoidifera), eight are strains identified to a genus and two are unidentified strains; in total, these strains represent at least 12 genera (electronic supplementary material, table S1). Phenotypic characteristics (whole-cell absorption spectra, cell size measurements, pigment concentrations, phycobiliprotein absorption spectra and PUR values) for 33 of the strains in this study were previously reported in Cunningham et al [14]. Specific characteristics of those strains plus the nine additional strains that we measured are listed in the electronic supplementary material, table S1.…”
Section: (A) Data Collectionmentioning
confidence: 73%
“…Phenotypic measurements were taken during exponential phase as determined by cell counts. Detailed culture conditions, methods for all phenotypic measurements and procedures for DNA extraction, polymerase chain reaction (PCR) amplification and sequencing are listed in the electronic supplementary material, S1 and follow Cunningham et al [14].…”
Section: (A) Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations